Fluidization 1980
DOI: 10.1007/978-1-4684-1045-7_57
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Fast Fluidization

Abstract: A mathematical model proposed for the Qynamics of fast fluidization to account for vertical voidage distribution, has been used to correlate the experimental data obtained in a 9-cm-diameter column with a height of 8 meters. The results are shown in a flow regime diagram spanning fran particulate and bubbling fluidization, through turbulent and fast fluidization, to dilute-phase pneumatic transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(104 citation statements)
references
References 2 publications
5
98
0
1
Order By: Relevance
“…In addition, the independent control of gas and solids retention times provides the reactor more flexibility in operation. Previous experiments have clearly demonstrated that CFB is hydrodynamically characterized by an extremely nonuniform flow structure, with a dense bottom region and dilute upper region in the axial direction [4][5][6] and a ''core-annulus'' flow structure in the radial direction. [7][8][9] This nonuniform flow structure and relatively dilute solids concentration (usually less than 10%) result in many disadvantages, such as the serious gas by-passing through the core dilute region and extensive backmixing of solids in the wall region, consequently resulting in lower gross gas-solids contact efficiency and poor selectivity of chemical reactions.…”
Section: Conventional Fluidized Bedmentioning
confidence: 99%
“…In addition, the independent control of gas and solids retention times provides the reactor more flexibility in operation. Previous experiments have clearly demonstrated that CFB is hydrodynamically characterized by an extremely nonuniform flow structure, with a dense bottom region and dilute upper region in the axial direction [4][5][6] and a ''core-annulus'' flow structure in the radial direction. [7][8][9] This nonuniform flow structure and relatively dilute solids concentration (usually less than 10%) result in many disadvantages, such as the serious gas by-passing through the core dilute region and extensive backmixing of solids in the wall region, consequently resulting in lower gross gas-solids contact efficiency and poor selectivity of chemical reactions.…”
Section: Conventional Fluidized Bedmentioning
confidence: 99%
“…Until now most research has been concentrated on hydrodynamics (Li and Kwauk, 1980;Weinstein et al, 1984;Rhodes and Geldart, 1987;Hartge et al, 1988;Horio, 1991) and heat transfer (Wu et al, 1989;Glicksman, 1988). Work to date has shown that the gas-solid flow in the circulating fluidized bed (CFB) riser is nonuniform, both axially and radially.…”
Section: Introductionmentioning
confidence: 98%
“…In the entrained-flow region the slip velocities again decrease with decreasing solids concentration. The fluidized-bed state diagrams discussed thus far, as well as others (e.g., [61], [62]), are suitable mainly for the qualitative interpretation of flow phenomena. A diagram proposed by Wirth (e.g., [10], [63], [64]) also provides quantitative assistance in the design of circulating fluidized beds.…”
Section: Hydrodynamic Principlesmentioning
confidence: 99%